Passions Secrètes : Collections privées flamandes. - David, Caroline; Baud-Berthier, Claire ([S.l.] : lille3000 & Vision Publishers, 2014)
Alÿs, Francis ; Andre, Carl ; Andrews, Kathryn ; Art & Language ; Barry, Robert ; Bellinkx, Ruben ; Beuys, Joseph ; Bogaert, Thomas ; Borremans, Michaël ; Bourgeois, Louise ; Braeckman, Dirk ; Bratkov, Sergey ; Buren, Daniel ; Fontaine, Claire ; Jackson, Matthew Day ; De Andrea, John ; De Bruyckere, Berlinde ; De Cordier, Thierry ; Delrue, Ronny ; Delvoye, Wim ; Devriendt, Robert ; Dijkstra, Rineke ; Dujourie, Lili ; Durant, Sam ; Eliasson, Olafur ; Elmgreen & Dragset ; Fabre, Jan ; Fleury, Sylvie ; Flood, Mark ; François, Michel ; Gordon, Douglas ; Graham, Dan ; Guyton/Walker ; Hodges, Jim ; Janssens, Ann Veronica ; Johnson, Rashid ; Kassay, Jacob ; Kelley, Mike ; Kiefer, Anselm ; Koester, Joachim ; Leroy, Eugène ; Lynch, Brendan ; Martin, Kris ; McCarthy, Paul ; McCarthy, Damon ; Messager, Annette ; Moffatt, Tracey ; Morimura, Yasumasa ; Muñoz, Juan ; Op de Beeck, Hans ; Opie, Julian ; Oursler, Tony ; Panamarenko ; Peyton, Elizabeth ; Pistoletto, Michelangelo ; Richter, Gerhard ; Rheims, Bettina ; Rotella, Mimmo ; Ruby, Sterling ; Ruff, Thomas ; Ronsse, Matthieu ; Sasnal, Wilhelm ; Schütte, Thomas ; Serrano, Andres ; Sierra, Santiago ; Snow, Dash ; Struth, Thomas ; Sultan, Larry ; Templeton, Ed ; Trecartin, Ryan ; Tuymans, Luc ; van den Broek, Koen ; Van de Velde, Rinus ; Van Dongen, Iris ; Clark, Kimberly ; Van Oost, Jan ; Verduyn, Jacques ; Vercruysse, Jan ; Vo, Dan ; Woodman, Francesca
Verborgen Passies. Vlaamse privé-Collecties, Tripostal, Rijsel, 10 oktober 2014 tot 4 januari 2015
boek